Tourism Industrialization Model and the Effects on the Income, Employment Opportunity, and Economy in Sumenep City, Beach 9, Gili Genting District - Arie Wahyu Prananta; Aminah Dewi Rahwawati; Syamsu Budiyanti; Jumi’atul Holisah; Widiyanto Kusumah (UIN Sunan Gunung Djati, 2022)
Urbanization in Indonesian increases quite significantly so that the tendency of the broadening economical social problems in many cities in Indonesia can cause national problems and become the social problems for Indonesian nation. Industrialization cannot be separated from the effort of improving the quality of human resource and the utilization of nature resources. In general, the relationship between development and industrialization. This study was expected to discover and develop SEM model where income distribution affected industrialization in Gili Genting District concentrated in three villages. Bon Baru Village, Bringsang Village, and Jate Lombang Village. This study uses quantitative methods and SEM (Structural Equation Modeling) analysis. we find that the Income Distribution affected Industrialization.